Web-Based Congregation Data Management Information System at Sumba Christian Church Kanjonga Bakul - Ningsi Tamu Ina; Yustina Rada; Desy Asnath Sitaniapessy (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
The rapid development of technology in the current era of globalization has provided many benefits in progress in various social aspects. Every action we take today is closely related to the use of technology, especially in the field of computerization and the internet. Data Management of the Sumba Christian Church (SCC) / Gereja Kristen Sumba (GKS) Kanjonga Bakul Congregation is one of the activities that must be carried out by the church every year, this activity is carried out by BPMJ officers or administrators and monitored by pastors. However, in GKS Kanjonga basket, the system for GKS Jamaat Data Management is still carried out by each congregation assembly to collect data conventionally by collecting photocopies of Family Cards and collecting data directly at each congregation house to recap back to the physical ledger. This process experienced various obstacles, including the difficulty in recapitulating the entire data managed, as well as the lack of efficiency in managing the data of the GKS Congregation. This conventional process leads to a waste of time and effort that should not be happening today, as well as a high risk of errors and inaccuracies in the recorded data. From the problem of data management of the GKS congregation in Kanjonga Bakul, this research will develop an Information System for the Management of Data of the Sumba Christian Church using the Rapid Application Development (RAD) method. The web development in this study will use the Hypertext Preprocessor (PHP) programming language with the CodeIgniter framework that implements the Model-View-Control (MVC) concept. This technology can optimize and improve the quality of data management of GKS congregations in Kanjonga Bakul.